COMPARATIVE ANALYSIS of LINEARLY POLARIZED PATCH ANTENNA for WI-FI and WLAN APPLICATIONS (International Journal of Engineering and Computer Science, 2014)
This paper presents novel compact, single feed, rectangular linearly polarized, Microstrip antenna for WI-FI and WLAN application, point to point and multipoint wireless communication. The proposed antennas fed by 50Ω impedance thin microstrip designed in both CST MWS and HFSS software. Proposed design shows tremendous return losses at frequencies of 4 GHz and 5GHz. 5 GHz band offers a clean radio environment for Wi-Fi without nuisance from virtually all non-Wi-Fi interference sources. The software used for the simulation is the CST Microwave Studio and HFSS which are an analytical tool that provides an accurate 3D EM simulation results for high frequency design. This work presents the comparison of two antenna analysis software and at the same time with the fabricated antenna.